2022
DOI: 10.1002/wer.10724
|View full text |Cite|
|
Sign up to set email alerts
|

Media selection for anammox‐based polishing filters: Balancing anammox enrichment and retention with filtration function

Abstract: Retrofitting conventional denitrification filters into partial denitrification‐anammox (PdNA)‐ or anammox (AnAOB)‐based filters will reduce the needs for external carbon addition. The success of AnAOB‐based filters depends on anammox growth and retention within such filters. Studies have overlooked the importance of media selection and its impact on AnAOB capacity, head loss progression dynamics, and shear conditions applied onto the AnAOB biofilm. The objective of this study was to evaluate viable media types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Given expanded clay higher surface roughness and higher iron content, it was hypothesized that increased PdNA rates would be achieved in the expanded clay due to high AnAOB retention efficiency previously observed in bench‐scale testing (Fofana et al, 2022). However, in this study, we observed similar PdNA rates of 840 ± 158 and 843 ± 196 g N/m 3 /d, and total nitrogen removal rates of 960 ± 125 and 964 ± 159 g N/m 3 /d for the sand and expanded clay filters, respectively (Figure 4, Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Given expanded clay higher surface roughness and higher iron content, it was hypothesized that increased PdNA rates would be achieved in the expanded clay due to high AnAOB retention efficiency previously observed in bench‐scale testing (Fofana et al, 2022). However, in this study, we observed similar PdNA rates of 840 ± 158 and 843 ± 196 g N/m 3 /d, and total nitrogen removal rates of 960 ± 125 and 964 ± 159 g N/m 3 /d for the sand and expanded clay filters, respectively (Figure 4, Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…No significant difference in performance was observed between the two media types although expanded clay was expected to have higher AnAOB growth and retention based on a previous bench-scale study (Fofana et al, 2022). The bumping and backwash applied in the pilot filters were automatically controlled based on head loss buildup, and the settings were similar for both media types.…”
Section: Lessons Learned and Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…For the latter carbon sources, it was hypothesized that having a good NO 2 À -N sink by efficient AnAOB retention is critical to provide efficient PdNA (Ladipo-Obasa et al, 2020;Riffat et al, 2021). For filters, it was shown that sand media was effective in retaining AnAOB under pilot scale conditions (Fofana, Peng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%